Real-Life Tolerability and Effectiveness of Adalimumab Biosimilar in Rheumatoid Arthritis: ASPIRE Registry Data - Sanjiv Kapoor; Viswanath V. Kaushik; Rahul Jain; Vijay Rao; Mihir Gharia (Rheumatology and Therapy, 2019)
Abstract Introduction The TNF-α blocker adalimumab is a well-proven therapy for rheumatoid arthritis (RA). A biosimilar adalimumab (ZRC-3197; Exemptia™), a ‘fingerprint match’ to reference adalimumab, has been approved for prescription in India since 2014. Here, we report on the effectiveness and tolerability of this biosimilar adalimumab (bADA) from the Adalimumab Biosimilar Patient Registry [ASPIRE; ISRCTN16838474], which contains data from real-life RA patients from India. Methods ASPIRE is a post-marketing, observational registry that evaluates real-world experience across multiple centres in India. Patients with moderate to severe RA who were prescribed bADA 40 mg subcutaneously every fortnight were enrolled. Patients with complete data available until 24 weeks of bADA treatment were extracted and analyzed for standard disease activity measures and reported adverse events. Results The registry included 149 patients with RA who had a median age of 41 (22–67) years; 65% of the patients were female. Disease outcome measures, i.e. ESR, DAS-ESR and VAS-pain scores, showed gradual and significant decreases (p < 0.0001 for all) in 73 analyzable patients who received 24 weeks of bADA therapy. ACR20, ACR50 and ACR70 responses were achieved in 48%, 48% and 34% of patients after 24 weeks of therapy, respectively, and about 58% and 15% of patients were moderate and good EULAR responders, respectively. Physician and patient ratings for the overall global assessment of efficacy and tolerability were ‘good’ to ‘excellent’ for the majority of the patients (≥ 96%). No new safety signals were observed when analyzing this registry data. Conclusion Real-life data from this post-marketing observational analysis demonstrate the clinical effectiveness and tolerability of 24 weeks of adalimumab biosimilar therapy in Indian patients with RA. This report also reflects upon the treatment strategies and prescription patterns for such therapies in Indian clinical practice. Trial Registration ISRCTN16838474. Funding Cadila Healthcare Limited, India.